Avaliação do potencial pozolânico da cinza de lodo de águas residuárias por meio de técnicas instrumentais - Rosa, Cristiane Maria da Silveira Thiago [UNESP] (2014)
Currently, there is a great concern for waste originating from sewage treatment plants. The system of wastewater treatment technique based on the activated sludge is widely used throughout the world, and basically consists in the separation of the solid part of the sewage through a dehydration process by centrifugation. The sewage, in a second phase of this process, it is sent to the reactors called Upflow Anaerobic Sludge Blanket (UASB), and, in that place, it is subjected to an anaerobic digestion, generating methane gas and anaerobic sludge. This sludge is sent to centrifuges and later released in buckets and transported to landfill. The final residue of this process has environmental concern since this material has been introduced directly in a landfill without a study on the possibility of other applications. Some applications of this material have been investigated by several researchers, for example, for producing biogas, fertilizers, and power generation. Nowadays, the civil construction industry is looking for the reuse of various types of residues in order to apply in the production of mortar and concrete. Some of them may have a pozzolanic property while others can be used as an addition (filler effect). The objective of this work is to evaluate the pozzolanic potential effect of the wastewater sludge ash through instrumental techniques, aiming at a future application in the production of mortar and concrete. Ashes were obtained after the realization of procedures of transporting, drying, grinding and calcining the sludge wastewater. After the tests of particle size measurement, of loss of mass in fire, of the content of chlorides and of insoluble residues, of diffraction and fluorescence of X-rays, of thermogravimetry, and of scanning electron microscopy, applied to the ashes and to the pastes that was made with them, it was possible to verify that this material has a pozolanic potential ...